Paciente de sexo masculino de 50 años de edad con diabetes mellitus tipo 2 y obesidad tipo 3. - Barco Goya, Keila Carolina (2020)
The following research work refers to a 50-year-old male patient with Obesity and Diabetes Mellitus II, who is referred to a nutritional consultation to control his weight and pathology. According to the anthropometric assessment, he refers to a body mass index of 40 kg / m2 which, according to the World Health Organization (WHO), is within the range of Type III Obesity with severe cardiovascular risk. In the research work (clinical case) the treatment and nutritional monitoring of the patient will be developed taking into account the anthropometric, biochemical, clinical and dietary indicators, in which a diet plan will be developed according to their caloric requirement, taking into account the tastes and diseases that the patient presents. The patient will be kept under constant surveillance by means of nutritional counseling, the patient will be guided which should be their adequate diet, in turn, make them take a favorable change in their eating habits so that their pathology can be managed correctly. The nutritional intervention carried out on the patient yielded positive results, managing to stabilize the patient, improving their physical condition, incorporating good eating habits, giving a noticeable change to their lifestyle, which was evidenced by the anthropometric data and laboratory tests carried out in the follow-up and monitoring of the patient.